Intellectuals Profetism in the Middle Criticism Political Reform - Jemali, Maksimilianus (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Politics is related to bargaining and interest. Politics triggers more people to intensively engage in it. Not only is the intensity ofparticipation revealed in the intellectual realm (analysis and discussion) but in the context of praxis as well.In a certain extent, there is a correlation of give –take concept between the academic and the politicalpraxis. The basis of analysis and the context of political praxis should be intensively addressed, so theexistence of politics and its meaning brings a positive impact for the people. Ideally, politics has goodintentions.Keywords: profetism, intellectual, reform, politics